2016
DOI: 10.3389/fpls.2016.00573
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of Soybean Leaves and Roots by iTRAQ Provides Insights into Response Mechanisms to Short-Term Salt Stress

Abstract: Salinity severely threatens land use capability and crop yields worldwide. Understanding the mechanisms that protect soybeans from salt stress will help in the development of salt-stress tolerant leguminous plants. Here we initially analyzed the changes in malondialdehyde levels, the activities of superoxide dismutase and peroxidases, chlorophyll content, and Na+/K+ ratios in leaves and roots from soybean seedlings treated with 200 mM NaCl at different time points. We found that the 200 mM NaCl treated for 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 67 publications
4
56
0
Order By: Relevance
“…Salinity is one of the major threats affecting land use capability and crop yield worldwide. Understanding the molecular mechanism governing the salt stress response will be a great asset to develop salt resistant crop plants (Ji et al, ). Salinity causes both ion toxicity and osmotic stress, and plants have developed a very complex salt tolerance mechanism during the course of evolution (Zhu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Salinity is one of the major threats affecting land use capability and crop yield worldwide. Understanding the molecular mechanism governing the salt stress response will be a great asset to develop salt resistant crop plants (Ji et al, ). Salinity causes both ion toxicity and osmotic stress, and plants have developed a very complex salt tolerance mechanism during the course of evolution (Zhu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Different types of TRxs were induced and regulated by abiotic stress in several plants (Zhang et al 2011;Chattopadhyay et al 2011;Ji et al 2016). An increase in TRx was seen in barley genotypes during salinity as well (Fatehi et al 2012a).…”
Section: Defense and Ros Scavengingmentioning
confidence: 99%
“…However, the mechanism of plant responses to salinity depends on the severity, duration of the stress, the growth conditions and the developmental stage of the plant, thus novel homeostasis between plant and environment at the proteome level will be established. 16,17 Up until now, little is known about the salt stress responses of darkgerminated soybeans at the proteome level. 18 Meanwhile, previous studies concerning proteomics were limited to 2dimensional gel electrophoresis (2-DE) analysis.…”
Section: Introductionmentioning
confidence: 99%
“…22 Studies have demonstrated that iTRAQ is an effective method to investigate DAPs in soybeans under different stressful physiological conditions. [23][24][25][26] To date, few studies have examined the darkgerminated soybean proteome under salt stress using iTRAQ methods.…”
Section: Introductionmentioning
confidence: 99%